Re-authoring identity conclusions in borderline personality disorder - Alicia Bruzek (International Journal of Narrative Therapy and Community Work, 2024)
This paper describes the use of narrative therapy with people who had been given a diagnosis of borderline personality disorder. In a context of significant stigma against persons with this diagnosis, perpetuated both within and beyond mental health systems, this paper shows how concepts of identity developed in narrative therapy were used to resist totalising identity conclusions and uncover possibilities for hope.